Geomorphometric Insights into the Dharla and Teesta River Basins through GIS and RS Methods - Bibi, Hafsa; Sifatul Hoque, Siam; Mahib, Reza; S M Sabbir, Hossen; A S M Zinnurain, Swadhin; K M Asif Iqbal, Akash; Khan Sarfaraz, Ali; Khandakar Hasan, Mahmud (INTI International University, 2025)
This study employs morphometric analysis using Geographic Information System (GIS) and Remote Sensing (RS) techniques to evaluate and compare the geomorphometric and hydrological characteristics of the Dharla and Teesta river basins in northern Bangladesh. Shuttle Radar Topography Mission (SRTM) Digital Elevation Model (30 m) data were used to delineate drainage networks and compute morphometric parameters from linear, areal, and relief aspects. Findings indicate that the Dharla River Basin (623.25 km²) is a fifth-order elongated basin characterized by moderate dissection, active erosion, and high flash flood vulnerability. In contrast, the Teesta River Basin (1,901.33 km²) exhibits a more complex drainage structure and regional-scale flooding patterns due to its Himalayan-fed origin and braided channels. By integrating SDG 6 (Clean Water and Sanitation) and SDG 13 (Climate Action), this research underscores the importance of morphometric assessment for sustainable watershed management, erosion mitigation, and climate-resilient flood control in northern Bangladesh.